Efficacy and safety of Botulinum Toxin A intradetrusor injections in adults with neurogenic detrusor overactivity/neurogenic overactive bladder: a systematic review - Soljanik, Irina (Drugs, 2013)
Botulinum toxin A (BoNTA) is increasingly used for therapy of neurogenic detrusor overactivity (NDO) refractory to antimuscarinics or where patients are experiencing antimuscarinic-related side effects.